Information, beliefs, and motivation: The antecedents to human resource attributions. (28th January 2019) - Hewett, Rebecca; Shantz, Amanda; Mundy, Julia
Summary: Despite significant interest in the attributions employees make about their organization's human resource (HR) practices, there is little understanding of the antecedents of HR attributions. Drawing on attribution theory, we suggest that HR attributions are influenced by information (perceptions of distributive and procedural fairness), beliefs (organizational cynicism), and motivation (perceived relevance). We test a model through a two‐wave survey of 347 academic faculty in the United Kingdom, examining their attributions of the purpose of their institution's workload management framework. After two preliminary studies (an interview study and a cross‐sectional survey) to establish contextually relevant attributions, we find that fairness and cynicism are important for the formation of internal attributions of commitment but less so for cost‐saving or exploitation attributions. Fairness and cynicism also interact such that distributive fairness buffers the negative attributional effect of cynicism, and individuals are more likely to attribute fair procedures to external forces if they are cynical about their organization. This study furthers the application of attribution theory to the organizational domain while making significant contributions to our understanding of the HR‐performance process.